Chemical Constituents and Biological Activity of Asam Aur Aur (Garcinia Parvifolia) and Jinggau (Ploiarium Alternifolium) - Ng, Sook Han (2007)
Chemical and biological studies were carried out on two plants, Garcinia parvifolia (Guttiferae) and Ploiarium alternifolium (Theaceae). The chemical investigations covered xanthones, benzophenones, anthraquinones, and triterpenes. The stem bark of Garcinia parvifolia and Ploiarium alternifolium were investigated and this resulted in the isolation of ten known compounds. These compounds were isolated using common chromatographic techniques and were identified by using spectroscopic experiments such as NMR, MS, IR and UV. Detailed chemical studies on Garcinia parvifolia have yielded two triterpenoids, stigmasterol and β-sitosterol, three xanthones, 6-deoxyjacareubin, daphnifolin and rubraxanthone, one benzophenone, isoxanthochymol and one alkaloid, caffeine. Meanwhile, investigations on Ploiarium alternifolium have afforded three anthraquinones, ploiariquinone A, emodin and 1,8-dihydroxy-3-methoxy-6-methyl-anthraquinone. The larvicidal test was carried out towards the larvae of Aedes aegypti. The crude chloroform, ethyl acetate and methanol extracts of Garcinia parvifolia were weakly active against the larvae of Aedes aegypti with LC50 values of 204.26, 194.96 and 236.44 μg/ml respectively while the crude chloroform extract of Ploiairum alternifolium was weakly active against the larvae of Aedes aegypti with an LC50 value of 159.12 μg/ml. The antimicrobial assay was carried out towards four pathogenic bacteria, Methicillin Resistant Staphylococcus aureus, Pseudomonas aeruginosa, Staphylococcus choleraesuis and Bacillus subtilis. For the microbes MRSA, P. aeruginosa and S. choleraesuis there were no inhibition by all the crude extracts of Garcinia parvifolia. The crude chloroform and methanol extracts of Ploiarium alternifolium showed no activity towards the microbe S. choleraesuis. Cytotoxic tests were performed using HL-60 Cell Line. The crude hexane, chloroform and ethyl acetate extracts of Garcinia parvifolia were considered to be active against the HL-60 cell line with IC50 values of less than 30 μg/ml. The rude chloroform extract of Ploiarium alternifolium was also considered to be active against the HL-60 cell line with an IC50 value of 23.3 μg/ml. The crude methanol extract of Ploiarium alternifolium showed the most significant activity with an IC50 value of 5.2 μg/ml. The antifungal activity testing of the plant extracts were carried out against the fungi Candida albican, Aspergillus ochraceaus, Sacchoromyces cerevisiae and Candida lypolytica. No activity was observed for all the crude extracts.